Monilethrix - Ahmad Qazi Masood; Hassan Iffat; Shah Parvaiz A (Wolters Kluwer Medknow Publications, 2002)
Monilethrix is a rare heritable disorder characterized by a structural defect of the hair with increased fragility. We here by report a case of monilethrix in a nine year old male child in view of the rarity of this condition.